Democratization and development A study on Paraclete Multi-Purpose Cooperative. - Tañega, Ma. Charine Q. (Tacloban City Ma. Charine Q. Tañega, 2009)
Cooperatives help in fostering democratization and development. They serve as intermediaries in delivering services and livelihood to the community and promote cooperation among individuals. Triumphant cooperatives are always born out of need. They cannot be imposed on a community rather they have to grow from the energy and commitment of the local people themselves.
Cooperatives integrate economic and social considerations in their objectives and tend to spread wealth and power to each member equally. Unlike government, which tends to be remote and unresponsive to the communities, it is supposed to serve and is driven by their members and reflects their needs.
This research is an in-depth study of the Paraclete Multi-Purpose Cooperative, a credit cooperative, situated in Tacloban City, Leyte. This study aims to evaluate the effectiveness and viability of the cooperative as well as its developmental functions in the context of democratization and development. It also revealed the achievements of the Paraclete Multi-Purpose Cooperative and shows evidence of their transformational capacity. It used a reliable framework which consisted of six (6) variables namely: (1) autonomy; (2) linkages; (3) participation (4) administrative capability; (5) financial capacity; and (6) developmental functions.
Based on the facts, I conclude that the Paraclete Multi-Purpose Cooperative has achieved a level of sufficiency in order to carry out its goals. However, it was not very effective in advancing developmental growth to the community. The members of the cooperative show enthusiasm and cooperate in the activities because of the perceived benefits they will get from the cooperative.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science